2019
DOI: 10.1111/conl.12652
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization as a conservation management tool

Abstract: The recent extensive loss of biodiversity raises the question of whether organisms will adapt in time to survive the current era of rapid environmental change, and whether today's conservation practices and policies are appropriate. We review the benefits and risks of inter‐ and intraspecific hybridization as a conservation management tool aimed at enhancing adaptive potential and survival, with particular reference to coral reefs. We conclude that hybridization is underutilized and that many of its perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 83 publications
0
122
0
Order By: Relevance
“…Briefly, three far northern colonies were individually crossed with three central colonies, resulting in 30 distinct familial crosses. We will hereafter refer to crosses as hybrids as defined by the nature of the intraspecific crosses (Chan et al, 2019). All 30 familial crosses were reared at 27.5°C.…”
Section: Coral Spawning Juvenile Settlement and Symbiosis Establishmentmentioning
confidence: 99%
“…Briefly, three far northern colonies were individually crossed with three central colonies, resulting in 30 distinct familial crosses. We will hereafter refer to crosses as hybrids as defined by the nature of the intraspecific crosses (Chan et al, 2019). All 30 familial crosses were reared at 27.5°C.…”
Section: Coral Spawning Juvenile Settlement and Symbiosis Establishmentmentioning
confidence: 99%
“…The genetic diversity parameters measure the degree of resemblance and difference in the genetic characteristics of individuals or the population and could therefore guide assisted hybridization processes by preventing associations of genetically closed individuals [23]. Much research has shown a greater performance in the biomass, speed of development, and fertility in progeny compared to those of both parents defined as heterosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular significance to this analysis, hybridization can lead to ‘genetic swamping’, where interbreeding with domestic cats produces hybrid populations in which no remaining individuals can properly be described as the native, wild cat species (Todesco et al, ). Incidentally, blurring taxonomic distinctions between wild cat species and domestic cats can undermine the application of species‐based conservation laws, where such distinctions determine whether a species is an appropriate focus for conservation action (Fitzpatrick, Ryan, Johnson, Corush, & Carter, , but see Chan, Hoffman, & Oppen, ).…”
Section: Domestic Cats and Wildlifementioning
confidence: 99%